1994
DOI: 10.1159/000213568
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Cytokine Secretion

Abstract: The aim of the present study was to compare cytokine secretion in healthy young and old subjects. Peripheral blood mononuclear cells were isolated from 55 healthy volunteers (aged 23-77 years) and cultured for 24 h in the presence or the absence of lipopolysaccharide (LPS) and 1,25-dihydroxyvita-min D3. Interleukin-lΒ (IL-1), tumor necrosis factor a (TNF) and prostaglandin E2 were measured in the culture superna-tants with specific immunoassays. The unstimulated and LPS-stimulated product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 6 publications
(9 reference statements)
2
36
1
1
Order By: Relevance
“…However, von Haehling et al (2003 determined that a significant correlation exists between age and TNF-α production by PBMCs. Riancho et al (1994) showed a positive correlation between age and IL-1β levels, but not TNF-α, in supernatants from isolated human monocyte cultures stimulated with LPS for 24 h. On the other hand, Bruunasgaard et al (1999) reported decreased levels of TNF-α and IL-1β in whole blood supernatants following LPS stimulation from the elderly, as compared to younger individuals. There was no difference with regard to IL-6 levels.…”
Section: Discussionmentioning
confidence: 98%
“…However, von Haehling et al (2003 determined that a significant correlation exists between age and TNF-α production by PBMCs. Riancho et al (1994) showed a positive correlation between age and IL-1β levels, but not TNF-α, in supernatants from isolated human monocyte cultures stimulated with LPS for 24 h. On the other hand, Bruunasgaard et al (1999) reported decreased levels of TNF-α and IL-1β in whole blood supernatants following LPS stimulation from the elderly, as compared to younger individuals. There was no difference with regard to IL-6 levels.…”
Section: Discussionmentioning
confidence: 98%
“…The mechanisms of such vulnerability to infections in the elderly have been ascribed to a breakdown in the anatomic barriers, underlying illnesses, or the declining capacity of the immune system [6][7][8][9]. Although many investigators have attempted to characterize the response to infection in aged animals, their attempts have produced equivocal results; some studies have shown a decreased response in aged hosts [10][11][12][13][14], while others have not [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…A similar argument may apply to the studies of Riancho et al [16] on human cells, which failed to demonstrate an age-related increase in PGEi production by activated peripheral blood mononuclear cells from healthy people, younger and older than 55 years. A trend of an increase, although statistically nonsignificant, in PGE2 production by Con A-stimulated splenocytes was noted in 24-month-old as compared to 3-month-old C57BL/6NNia mice [12], in line with our data on 18-to 23-month-old mice in the present study.…”
Section: Discussionmentioning
confidence: 62%